Application of cross cables for the flutter stability of a long-span suspension bridge during erection. (1st February 2023) - Tang, Haojun; Li, Yongle; Mo, Wei
Highlights: Installation of cross cables improves flutter stability of the bridge during erection. Modal characteristics between two main spans are determined for different stages. Suppression mechanism of cross cables changes with the increasing girder length. Effects of static and dynamic wind loads on cross cables are further revealed. Abstract: Long-span suspension bridges during erection show more flexible dynamic characteristics and worse flutter performance. The aerodynamic optimization may make the flutter performance meet the requirement, but some countermeasures are costly or difficult to realize. Therefore, it is necessary to design some practicable structural countermeasures which could improve the dynamic characteristics of long-span suspension bridges during erection and so does their flutter stability. This paper takes a long-span suspension bridge with two main spans as the example. The effect of cross cables on the structural dynamic characteristics is studied, and the critical flutter state of the bridge is accurately determined by the most unfavorable modal combination. The reason why the flutter stability could be improved is revealed by changing the stiffness of the cross cables. The wind-induced static and dynamic response of the bridge is further discussed, and the effectiveness of the cross cables at high wind speeds is evaluated. The results show that the installation of the cross cables on the free ends of the girders is favorable to the flutter performance of the bridge during erection. When the bridge is equipped with the cross cables, the association between the girder lateral bending and torsion will be enhanced for later erection stages with longer suspender girder lengths, which should be taken into account in the flutter analysis. With the static wind loads, the cross cables on one side are in compression and lose the effectiveness, but the cross cables on the other side could still improve the flutter performance of the bridge. As the internal force fluctuates significantly, the cross cables and the temporary connections should have enough strength.